Educational program on fatigue for brain tumor patients: possibility strategy? - Bigatão, Marcela dos Reis; Peria, Fernanda Maris; Tirapelli, Daniela P. C.; Carlotti, Carlos Gilberto, Junior (Arquivos de Neuro-Psiquiatria, 2016)
Objective To evaluate the effectiveness of an educational program on improvement of fatigue and quality of life of patients with high-grade glioma during radiotherapy and chemotherapy treatment.Method This is a longitudinal, experimental study. Twenty-three patients with high-grade glioma were randomly assigned to one of two groups. Both groups completed the Functional Assessment of Cancer Therapy: Fatigue questionnaire and the Beck Depression Inventory, and one of the groups received the educational intervention. The groups did not show any change in quality of life and fatigue in this study, for this reason, the educational program did not present any significant difference. However, there was a significant difference in depressive symptoms during the educational program showing positive evidence for its applicability.
Keywords: glioma; fatigue; depression; quality of life; health education